(untitled) (Al-Academy, 2023)
With a descriptive and analytical approach, it discusses the concept of phenomenology as an approach to seeing the aesthetics of ugliness as one of the concepts associated with the aesthetic experience in contemporary art designs, as it is the result of communication between artistic production and the recipient, which leads to creating a state of aesthetic pleasure. A phenomenological method is used to uncover the aesthetics of ugly and to connect ugliness and beauty since ugliness in aesthetics incorporates beauty as a modern aesthetic vision from the phenomenological perspective. The study investigated aesthetics as a phenomenon of perception, sensory knowledge, and the aesthetic response to the production of designs in contemporary art, represented by achieving a status of aesthetic pleasure, and the phenomenological approach can be applied to see the aesthetics of ugliness in contemporary design, and there is a relationship between the aesthetics of ugliness and the aesthetic experience in producing contemporary design, and it reached the possibility of applying the phenomenological approach to appreciation and criticism with an aesthetic vision of ugliness, by transforming the influence of phenomenological thought as a method into an aesthetic concept. To build the design for a more in-depth vision in a new analytical reading, and to have a merit in the study and production of designs that began with the art of the event and ended as digital art with technical effects, with its components (intentionality).